Student Academic Dishonesty: The Potential for Situational Prevention. Issue 1 (2nd January 2016) - Hodgkinson, Tarah; Curtis, Hugh; MacAlister, David; Farrell, Graham
Abstract : Approximately one-half to three-quarters of university students commit some form of cheating, plagiarism, or collusion. Typical university responses are policy statements containing definitions plus punishment procedures. This paper collates a portfolio of strategies and tactics that seek to design-out, deter, and discourage academic misconduct. It finds many routine tactics exist, from silence and the use of large halls for major exams, to restrictions on electronic devices. Others are less consistently adopted, such as splitting lengthy exams in two to discourage washroom-visits where cheating takes place. The portfolio of tactics is framed in the context of crime opportunity theory and the 25 techniques of situational crime prevention. It is proposed that more consistent application of tactics focusing on environmental design, curricular design, and class management offer significant potential for reducing misconduct. Future research should seek to evaluate and enhance such interventions.